Agricultural Drone Zoning and Deployment Strategy with Multiple Flights Considering Takeoff Point Reach Distance Minimization - Singgih, Ivan Kristianto (Universitas Komputer Indonesia, 2021)
In the agricultural sector, drones are used to spray chemicals for the plants. A lawn mowing movement pattern is one of the widely used methods when deploying the drones because of its simplicity. A route planner determines some pre-set routes before making the drones to fly based on them. Each drone flight is limited by its battery level or level of spray liquids. To efficiently complete the spraying task, multiple drones need to be deployed simultaneously. In this study, we study a multiple drone zoning and deployment strategy that minimizes the cost to set up equipment at the takeoff points, e.g., between flights. We propose a method to set the flight starting points and directions appropriately, given various target areas to cover. This is the first study that discusses the spraying drone zoning and deployment plan while minimizing the number of takeoff points, which plays an important role in reducing the drone set up and deployment costs. The suggested procedure helps drone route planners to generate good routes within a short time. The generated routes could be used by the planner for their chemical spraying activity and could be used as initial input for their design, which can be improved with the planners’ experience. Our study shows that when generating an efficient route, we must consider the number of flight area levels, directions of the drone movements, the number of U-turns of the drones, and the start points of the drone flights